Apse - Ghosh, Ayan (2023)
Famously known as the "Bullion King of Mumbai," Premchand Roychand was a benefactor to St. Thomas Cathedral. His generous contributions helped complete renovations, which lasted from 1862-1867 and resulted in an enlarged apse, chancel, and organ chamber (seen here). It cost Rs 1,63,000, which was partly raised by public donations, and the rest was funded by the government.